(No) Haircut for Hellas?: A Short and Critical Reply to Armin Steinbach, 'The "Haircut" of Public Creditors under EU Law', 13 EuConst (2016) p. 223. (7th November 2016) - Thiele, Alexander
Abstract : Smouldering European debt crisis: overall public debt ratio as problem – Haircut as possible solution – Greece's current creditors: public institutions (Member States and European Central Bank) – Insuring a sound budgetary policy as main goal of Article 125 TFEU – Consequences for a haircut by the Member States – The mandate of the European Central Bank and the prohibition of direct purchases of Member State bonds – Consequences for a haircut by the European Central Bank – Haircut as political question open for democratic debate